NUTRITION PROGRAM TERHADAP PENURUNAN KEJADIAN STUNTING PADA BALITA : SYSTEMATIC REVIEW - Azwar, Azwar; Rekawati, Etty; Setiawan, Agus; Rahmadiyah, Dwi Cahya (Jurnal Kesehatan, 2023)
Background: Stunting is a nutritional disorder that results in growth failure in young children. One intervention that can be done is the nutrition programme. Objective: This study identifies the impact of nutrition programme interventions on reducing the incidence of stunting in toddlers. Methods: This study used a systematic review approach from the scince direct database, clinical key for nursing, francis & taylor and Ebsco Host. The articles used were research results published between 2019 - 2023 with search techniques using the PRISMA method. Results: The search found 7 articles. Based on these findings, it shows that the nutrition programme has an influence in the process of reducing the incidence of stunting in toddlers through the provision of adequate nutrition to toddlers. Conclusion: nutrition programmes can be used as one of the community-based interventions in an effort to reduce the incidence of stunting.